Exploring The Impact of Integrating Problem Based Learning and Agile in the Classroom on Critical Thinking - Churiyah, Madziatul; Arief, Mohammad; Permansyah, Sigit (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2024)
The purpose of this study was to improve critical thinking skills and student learning outcomes at SMK Negeri 1 Probolinggo through the implementation of problem-based learning models. This type of research is classroom action research which consists of 2 cycles where each cycle has 2 meetings. This research has two types of data, namely quantitative data and qualitative data. Obtaining research data obtained through initial observation, interviews with teachers and students, tests at the end of the cycle, documentation, and field notes. Data analysis is done by reducing data, presenting data, and drawing conclusions. The results of the research show that the problem-based learning process is used to stimulate critical thinking in problem-oriented situations. The researcher was assisted by 3 observers who observed the course of the learning process. Students' critical thinking skills on the indicators of managing strategies and tactics obtain a high percentage because the giving of actions is carried out by utilizing media. Genially with gamification features so that they affect learning outcomes which experience an increase in each cycle.